Nimodipine Exerts Beneficial Effects on the Rat Oligodendrocyte Cell Line OLN-93 - Boltz, Felix; Enders, Michael; Feigenspan, Andreas; Kirchner, Philipp; Ekici, Arif Bülent; Kürten, Stefanie (Brain Sciences, 2022)
Multiple sclerosis (MS) is a chronic autoimmune disease of the central nervous system (CNS). Therapy is currently limited to drugs that interfere with the immune system; treatment options that primarily mediate neuroprotection and prevent neurodegeneration are not available. Here, we studied the effects of nimodipine on the rat cell line OLN-93, which resembles young mature oligodendrocytes. Nimodipine is a dihydropyridine that blocks the voltage-gated L-type calcium channel family members Cav1.2 and Cav1.3. Our data show that the treatment of OLN-93 cells with nimodipine induced the upregulation of myelin genes, in particular of proteolipid protein 1 (Plp1), which was confirmed by a significantly greater expression of PLP1 in immunofluorescence analysis and the presence of myelin structures in the cytoplasm at the ultrastructural level. Whole-genome RNA sequencing additionally revealed the upregulation of genes that are involved in neuroprotection, remyelination, and antioxidation pathways. Interestingly, the observed effects were independent of Cav1.2 and Cav1.3 because OLN-93 cells do not express these channels, and there was no measurable response pattern in patch-clamp analysis. Taking into consideration previous studies that demonstrated a beneficial effect of nimodipine on microglia, our data support the notion that nimodipine is an interesting drug candidate for the treatment of MS and other demyelinating diseases.
CRIS-Team Scopus Importer:2022-05-06
Keywords: dihydropyridines; MS; myelination; neuroprotection; nimodipine; OLN-93